Oxonium ions, rearrangements, and natural products - Chan, H (2019)
This thesis focuses on the studies of a set of biologically relevant oxonium ions pertinent to the natural product biosynthesis of the red algae of the genus Laurencia. The total synthesis of these oxonium ions is reported along with their structural elucidation supported by extensive NMR spectroscopic analysis and DFT computations. The biosynthetic significance of these oxonium ions is demonstrated by their direct derivatisation into 12 natural products, namely (Z/E)-bromofucins, (Z/E)-chlorofucins, (Z/E)-elatenynes, laurendecumenyne B, laurefurenyne E, laurefurenyne F, ent-(Z/E)-laurefucins and ent-acetyllaurefucin. Furthermore, 6 additional natural products are synthesised indirectly from the oxonium ions, namely (Z/E)-notoryne, laurefurenyne C, laurefurenyne D, ent-deacetyllaurencin and ent-laurencin. The total synthesis of laurefurenynes C-F also enabled their structural reassignment. Chapters 1-3 of this thesis introduce the project, provide a brief summary of the chemistry of oxonium ions, and an overview of the proposed biosyntheses of Laurencia natural products. Chapters 4-6 report the total synthesis of the oxonium ions, their characterisation and their direct derivatisation into various natural products. Chapters 7-8 concerns the total synthesis of ent-deacetyllaurencin, ent-laurencin and the total synthesis of laurefurenyne C-F and their structural reassignment.